Germplasm conservation of economically important medicinal plant Nyctanthes arbor-tristis L. through encapsulation technique and maintenance under slow growth condition - Mishra, Awadhesh Kumar; Tiwari, Kavindra Nath; Mishra, Pallavi; Mishra, Sunil Kumar; Tiwari, Shailesh Kumar (Springer Science and Business Media B.V., 2022)
An efficient encapsulation and slow growth conservation protocol was developed for Nyctanthes arbor-tristis L. an antiviral medicinal plant of the family Oleaceae. A gel matrix with 3% sodium alginate and 100 mM calcium chloride (CaCl2⋅2H2O) was found best for the encapsulation of nodal segments. The viability and shoot development potential of encapsulated nodal segments was optimized. Encapsulated nodal segments stored at 4 °C and 24 °C remained viable for up to 90 days and showed shoot development potential 42.89 ± 6.04% and 33.53 ± 7.15% respectively. Nodal segments maintained under slow growth conditions up to 180 days on one-eighth strength Murashige and Skoog (MS) medium supplemented with 0.5% sucrose was suitable for satisfactory viability (40.28 ± 2.04%), while further addition of 0.5 mg/l abscisic acid supported 40.36 ± 1.01% viability of the nodal segments. The best rooting response was achieved on half-strength MS medium supplemented with 4 mg/l indole-3-acetic acid. The field survival of rooted plants was 65%. The clonal fidelity of in-vitro derived plantlets was studied with start codon targeted primer profile, which showed the same banding mobility patterns as the source parent plant. The maximum banding profile was monomorphic and consistent, confirming the clonal stability of regenerated plants. The method developed will permit the in-vitro conservation of this species and facilitate an easy exchange of plant germplasm.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Abscisic acid; Encapsulated propagules; Nyctanthes arbor-tristis L; Slow growth; Start codon targeted prime; Calcium Chloride; Conservation; Encapsulation; Hardiness; Plants; Sodium Alginate; Plants (botany); Sodium; Abscisic acid; Encapsulated propagules; Germplasms; Growth conditions; Medicinal plants; Nyctanthes arbor-tristi L; Propagules; Slow growth; Start codon targeted primer; Start codons